KOMUNIKASI ANTARPERSONA ANAK DENGAN ORANGTUA DALAM MENCEGAH KEKERASAN - Fardiah, Dedeh; Rinawati, Rini (Universitas Mercu Buana, 2016)
The family becomes the starting place for a child's growth. Therefore, the family needs to provide the process of education and a sense of security in children. This is understandable because currently the graph of violence against children the number tends to rise from year to year. The problem of violence is a phenomenon of icebergs, in fact not all victims of violence often report their cases for various reasons. Based on the results of the author's research, communication made by parents in preventing violence in children gives an idea that communication between parents parent to child has contributed to the process of preventing violence in children. On the other hand, interpersonal communication between the child and the parent needs to be done to see the whole family communication in preventing violence that occurs in the child. Based on the phenomenon described it is interesting to examine how: